ECOLOGICAL THEOLOGY IN INDONESIAN CHRISTIAN SCHOLARSHIP: A SYSTEMATIC LITERATURE REVIEW OF ECOTHEOLOGY, 2000–2025 - Sekry Evan Sandiata; Vanny Nancy Suoth; Denny Adry Tarumingi; Rivay Bobby Palempung; Valdo Vreden Woruntu (SOSIOEDUKASI, 2025)
Ecological crises in Indonesia, such as rapid deforestation, the spread of mining, loss of biodiversity, climate, and frequent disasters, overlap with each other and require more frequent theological and technical solutions (Margono et al., 2014; Sodhi et al., 2004; Steffen et al., 2015). As the largest archipelagic state in the world, with Christian communities of different denominations widely distributed throughout the country, Indonesian Christian scholarship has begun to develop particular models of ecological theology. However, this new area is still divided, and there is not much systematic systematization of its thematic, methodological, and contextual developments (Golo and Yusuf 2018). In this article, a systematic literature review on the topic is conducted using PRISMA to examine Indonesian Christian ecotheology to from 20002025. Nine databases of academic sources ( Scopus, Web of Science, Atla Religion Database, ProQuest Religion and Philosophy, EBSCOhost, DOAJ, GARUDA, Neliti, and major repositories of theological collections) revealed 1,847 records, and 68 studies were selected after screening and eligibility tools. Quality appraisal was an integration of the Mixed Methods Appraisal Tool (MMAT) (used to assess empirical works) (Hong et al., 2018) and a modified theological assessment framework (Vanhoozer, 2005; Schreiter, 1985). Data synthesis was performed based on descriptive statistics, mapping of key word co-occurrence, and thematic analysis (Sandelowski et al., 2006; Thomas and Harden, 2008). The results indicate rapid growth since 2016, denominational diversity, and five master themes: doctrinal foundations, indigenous cosmologies and land/sea relations, ecclesial practices and eco-spirituality, public and justice-oriented ecotheology, and methodological developments. Indonesian ecotheology also contributes to the global discourse through its adat, archipelagic and disaster experiences, and postcolonial critique, although there are still gaps in Papua-Maluku ecotheology, Pentecostal ecotheology, marine theology and urban theology, and outcome-oriented research.